"We felt they took the heart out of the community": Examining a community-based response to urban school closure - Terrance Green (Arizona State University, 2017)
Massive school closures are occurring in urban school districts across the United States. Research suggests that school closures are the outcome of racialized neoliberal policies and decades of disinvestment that have left many urban districts with fiscal deficits and declining student enrollments. However, some urban communities have successfully organized against school closures and reopened neighborhood schools. As such, this study examines how leaders in a community-university coalition in the Midwestern United States reopened a high school that was closed by its district. This case study draws on interviews and document data, and describes the forces that promoted school closure and its impacts on the community. Concepts from social capital and social network theories are used to guide the analysis. Findings indicate these leaders leveraged networks to negotiate a community-university social contract, took strategic and socially connected actions, and formed a community-driven education task force. This study offers implications for policy, future research, and communities in similar contexts.